Plasma let-7i and miR-15a expression are associated with the effect of recombinant tissue plasminogen activator treatment in acute ischemic stroke patients. Issue 158 (October 2017) - Xiang, Wei; Tian, Canhui; Lin, Jingru; Wu, Xiaohui; Pang, Guanlai; Zhou, Liang; Pan, Suyue; Deng, Zhen
Abstract: Circulating microRNAs (miRNAs) have been reported as diagnosis biomarkers and predictors in acute ischemic stroke (AIS). However, how the expression of circulating miRNAs changes after recombinant tissue plasminogen activator (rt-PA) treatment in AIS patients is still unknown. Objective: To determine the expression of circulating miRNAs in AIS patients receiving rt-PA treatment and those not receiving it. Methods: Blood samples were collected 24 h after onset from 40 AIS patients receiving rt-PA treatment and 46 AIS patients (admission at 8–24 h of onset) not receiving rt-PA treatment. Thirty-nine age- and sex-matched healthy volunteers were used as the control group. We used miRNA microarrays to detect plasma miRNA expression and real-time PCR to verify miRNA expression. Results: Compared to the non–rt-PA treatment group, the rt-PA treatment group showed 16 differentially expressed miRNAs. The change in the expression of let-7i and miR-15a was confirmed by real-time PCR. Compared to the heathy controls, the non–rt-PA group showed decreased let-7i expression and the rt-PA group showed a 4-fold increased let-7i expression. The let-7i expression was also found to correlate with the National Institute of Health stroke scale (NIHSS) score (rho = 0.297, P = 0.005). On the contrary, miR-15a expression decreased by 0.5-fold in the rt-PA group compared to that in the non-rt-PA group. Conclusion: The circulating miRNAs let-7i and miR-15a showed differential expression between AIS patients receiving thrombolysis treatment (rt-PA group) and those not receiving it (non-rt-PA group). Compared to the non-rt-PA group, the rt-PA group showed upregulation of let-7i and downregulation of miR-15a. Highlights: Plasma miRNAs differentially expressed in acute ischemic stroke patients who receiving rt-PA treatment and those not. Circulating let-7i were decreased in stroke patients but increased in rt-PA treatment patients compared to health control. Plasma miR-15a were downregulated in rt-PA treatment patients compared to stroke and health control.